A cost-effective, environmentally-aware undersea infrastructure to enhance community resilience to tsunamis. (December 2016) - Xerandy,; Znati, Taieb; Comfort, Louise K.
Highlights: A cost effective, tsunami alert notification underwater network infrastructure. An underwater network which combines undersea sensors and fiber optic. Optimization model that incorporates environment factors and realistic channel model. Heuristic approach to find near-optimal solution of the derived optimization problem. Cost analysis to explore the feasibility of the approach under different scenarios. Abstract: The focus of this paper is on mitigating the impact of near-field tsunami detection on humans and the environment. We propose a hybrid network infrastructure that combines an undersea sensor network with fiber optic cable for cost effective, timely, and reliable near-field tsunami detection. We first formulate a cost minimization problem for near-field tsunami detection. To capture important characteristics of the environment, the optimization model incorporates into its formalization important sea environment factors and a realistic acoustic propagation model. A heuristic approach is developed to derive a near-optimal solution to the original cost minimization problem. To demonstrate the viability of the proposed model, a case study, focused on Padang City is used, and a comparative analysis of different network configurations, using different design parameters and cost scenarios is performed. Three different cost functions, namely linear, power-law, and logarithmic, are used in the analysis. The results show that the heuristic computes efficient network configurations when a solution exists, for the linear, logarithmic, and power-law cost functions. However, further assessment should be made on the results to anticipate a local maximum that may exist in the cost function.